Relationship between changes in total-body water and fluid distribution with maximal forearm strength in elite judo athletes - Silva, A. M.; David, A.; Heymsfield, S. B.; Sardinha, L. B. (The Journal of Strength and Conditioning Research, 2011)
Among judo athletes, strong grip strength is crucial for performing offensive and defensive maneuvers that rely predominantly on forearm maximal strength (FMS). The study aims were to evaluate changes in total-body water (TBW) and its compartments (extracellular water [ECW] and intracellular water [ICW]) and their relationship with loss of FMS in elite judo athletes. At baseline (weight stability), 27 male elite athletes were evaluated (age: 23.2 ± 2.8 years) and again evaluated 1-3 days before competition. Athletes were free to gain or lose weight based upon their specific competition needs. Using dilution techniques (deuterium and bromide), TBW and ECW were estimated, and ICW was calculated (ICW = TBW - ECW). Fat, fat-free mass, and appendicular lean soft tissue (LST) were assessed by dual-energy x-ray absorptiometry. Handgrip was used to assess FMS. Using a reduction of 2% as a representative outcome for decreased FMS, 10 athletes were identified as having lost FMS, whereas 17 changed <2% or gained. Comparison of means and logistic regression analysis were performed. Results from baseline to before competition indicated that those who lost >2% of FMS significantly decreased TBW and ICW by -2.7 ± 3.0 and -4.4 ± 4.2%, respectively. The groups differed in ICW changes (-4.4 ± 4.2 vs. 1.9 ± 6.1%), respectively, for those who lost FMS by >2%. The ICW changes, but not in TBW or ECW, significantly predicted the risk of losing FMS (beta = 0.206; p = 0.027), even adjusting for weight and arm LST changes. These findings indicated that reductions in ICW increased the risk of losing grip strength in elite judo athletes.